2023
DOI: 10.1371/journal.pone.0273883
|View full text |Cite
|
Sign up to set email alerts
|

Impact of galvanic vestibular stimulation electrode current density on brain current flow patterns: Does electrode size matter?

Abstract: Background Galvanic vestibular stimulation (GVS) uses at least one electrode placed on the mastoid process with one or multiple placed over other head areas to stimulate the vestibular system. The exact electrode size used is not given much importance in the literature and has not been reported in several studies. In a previous study, we compared the clinical effects of using different electrode sizes (3 cm2 and 35 cm2) with placebo but with the same injected current, on postural control. We observed significa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Computational modeling and simulation such as the one reported here is now increasingly used across a range of stimulation modalities, from optimizing delivery, performing safety analysis, to supporting device design / development [29,39 50-53]. Furthermore, these predictions have helped in elucidating stimulation parameter choices, understanding mechanism of action, explaining stimulation outcome, and thereby advancing stimulation administration in general [11, 5457]. We expect this study on the arm to guide researchers in performing future explorations on other body parts, determine ideal pulse width range for target nerve of interest, attempt validation using TENS similar to the one performed in MS [23], and investigate new TENS delivery approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling and simulation such as the one reported here is now increasingly used across a range of stimulation modalities, from optimizing delivery, performing safety analysis, to supporting device design / development [29,39 50-53]. Furthermore, these predictions have helped in elucidating stimulation parameter choices, understanding mechanism of action, explaining stimulation outcome, and thereby advancing stimulation administration in general [11, 5457]. We expect this study on the arm to guide researchers in performing future explorations on other body parts, determine ideal pulse width range for target nerve of interest, attempt validation using TENS similar to the one performed in MS [23], and investigate new TENS delivery approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller sized electrodes, providing higher current density over a smaller area, resulted in a significant improvement in balance compared to the 35 cm 2 electrodes, that provided results that were no different to sham stimulation. Truong et al (2023) modeled the electrical effect of both 3, and 35cm 2 electrodes and reported the smaller electrode provided a more focal stimulation of the vestibular apparatus and temporal cortex, whereas there was more current loss via the skull and cerebrospinal fluid using a 35cm 2 electrode. To afford further support for the observation that smaller electrodes provide more specific, localized stimulation of the vestibular system, the size, shape and material of electrodes, and details around the electrode-skin interface, should be clearly reported.…”
Section: Integrated Analysis and Discussionmentioning
confidence: 99%